Karyopherin Alpha 2-Expressing Pancreatic Duct Glands and Intra-Islet Ducts in Aged Diabetic C414A-Mutant-CRY1 Transgenic Mice - Satoshi Okano; Akira Yasui; Shin-ichiro Kanno; Kennichi Satoh; Masahiko Igarashi; Osamu Nakajima (Journal of Diabetes Research)
Our earlier studies demonstrated that cysteine414- (zinc-binding site of mCRY1-) alanine mutant mCRY1 transgenic mice (Tg mice) exhibit diabetes characterized by the reduction of β-cell proliferation and by β-cell dysfunction, presumably caused by senescence-associated secretory phenotype- (SASP-) like characters of islets. Earlier studies also showed that atypical duct-like structures in the pancreas developed age-dependently in Tg mice. Numerous reports have described that karyopherin alpha 2 (KPNA2) is highly expressed in cancers of different kinds. However, details of the expression of KPNA2 in pancreatic ductal atypia and in normal pancreatic tissues remain unclear. To assess the feature of the expression of KPNA2 in the development of the ductal atypia and islet architectures, we scrutinized the pancreas of Tg mice histopathologically. Results showed that considerable expression of KPNA2 was observed in pancreatic β-cells, suggesting its importance in maintaining the functions of β-cells. In mature stages, the level of KPNA2 expression was lower in islets of Tg mice than in wild-type controls. At 4 weeks, the expression levels of KPNA2 in islets of Tg mice were the same as those in wild-type controls. These results suggest that the reduction of KPNA2 might contribute to β-cell dysfunction in mature Tg mice. Additionally, the formation of mucin-producing intra-islet ducts, islet fibrosis, and massive T cell recruitment to the islet occurred in aged Tg mice. In exocrine areas, primary pancreatic intraepithelial neoplasias (PanINs) with mucinous pancreatic duct glands (PDGs) emerged in aged Tg mice. High expression of KPNA2 was observed in the ductal atypia. By contrast, KPNA2 expression in normal ducts was quite low. Thus, upregulation of KPNA2 seemed to be correlated with progression of the degree of atypia in pancreatic ductal cells. The SASP-like microenvironment inside islets might play stimulatory roles in the formation of ductal metaplasia inside islets and in islet fibrosis in Tg mice.